The Factors of Management, Communication, Partnership, and Innovation in the Implementation of Posbindu (Integrated Health Post) NCD: A Study in Kelurahan Gunung Batu Bogor City - Parinduri, Siti Khodijah; Pujiyanto, Pujiyanto (Journal of Indonesian Health Policy and Administration, 2018)
By 2015, 68% of deaths in Indonesia are due to non-communicable diseases (NCD) and are forecast to increase to 74% by 2030. Riskesdas data of 2013 show that 69.6% of cases of diabetes mellitus and 63.2% of cases of hypertension have not been diagnosed. The government has been trying to proactively make efforts to prevent NCD through the implementation of Posbindu (Integrated Health Post) NCD, but visit Posbindu NCD in the work area of Pasir Mulya Puskesmas, Bogor City is very diverse. The purpose of this study is to analyze the factors of management, communication, partnership, and innovation in the implementation of Posbindu NCD and determinants of the implementation of Posbindu NCD. We conducted in-depth interviews, focus group discussions, document review and observation at two Posbindu NCD with the highest number of visits and the lowest in Gunung Batu Village, Bogor City in 2017. We interviewed 15 informants, consisting of cadres, in charge of NCD Puskesmas, in charge of Puskesmas Pembantu and supervisor of Posbindu NCD. This research found 4 factors, namely management (human resources, fund, and facilities), innovation, communication and partnership that influence the result of Posbindu implementation. Therefore, to run effectively the Posbindu NCD program, then 4 of those factors need to be optimized